2015
DOI: 10.1021/es5053396
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Physicochemical Properties to the Antioxidative Activity of Free Amino Acids in Fenton System

Abstract: Herein we compared antioxidative activities (AA) of 25 free L-amino acids (FAA) against Fenton system-mediated hydroxyl radical (HO(•)) production in aqueous solution, and examined the relation between AA and a set of physicochemical properties. The rank order according to AA was: Trp > norleucine > Phe, Leu > Ile > His >3,4-dihydroxyphenylalanine, Arg > Val > Lys, Tyr, Pro > hydroxyproline > α-aminobutyric acid > Gln, Thr, Ser > Glu, Ala, Gly, Asn, Asp. Sulfur-containing FAA generated different secondary reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Still, we cannot be absolutely sure that HS • radical is not produced in the system, because spin adduct (DEPMPO/SH) might show a very brief lifetime due to strongly reducing conditions. Such problem has been observed previously for cysteine thiyl radical [34]. Finally, a possibility that HS -/H 2 S could provoke a release of copper from CuZnSOD and to maintain it in 'free' Cu 1+ form (Cu 2+ in buffer solution shows a strong EPR signal [35]) can be excluded in accordance with findings that hydrogen sulfide promotes the M A N U S C R I P T…”
Section: Hssupporting
confidence: 85%
“…Still, we cannot be absolutely sure that HS • radical is not produced in the system, because spin adduct (DEPMPO/SH) might show a very brief lifetime due to strongly reducing conditions. Such problem has been observed previously for cysteine thiyl radical [34]. Finally, a possibility that HS -/H 2 S could provoke a release of copper from CuZnSOD and to maintain it in 'free' Cu 1+ form (Cu 2+ in buffer solution shows a strong EPR signal [35]) can be excluded in accordance with findings that hydrogen sulfide promotes the M A N U S C R I P T…”
Section: Hssupporting
confidence: 85%
“…The enhanced availability of GSH was associated with transcriptional upregulation of GSS, a gene encoding glutathione synthase involved in GSH biosynthesis. In addition, the hydroxyl group on the pyrrolidine ring in Hyp can stabilize free radicals such as hydroxyl radical, which might be implicated in and contribute to its antioxidative effects in response to DSS treatment . Considering the functional role of ROS in the initiation and promoting inflammatory response in IBD patients and experimental colitis in mice, Hyp supplementation reduced ROS level, therefore conferring a protective effect in the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Castro and co‐workers reported that Hyp is capable of reacting with free radicals generated from the decomposition of carbon tetrachloride catalyzed by benzoyl peroxide . In a recent study, Hyp has been observed to act with hydroxyl radicals generated from the Fenton reaction, indicating an antioxidative capacity . These findings indicate that Hyp may serve as a potential ROS scavenger and regulate the cellular redox state.…”
Section: Introductionmentioning
confidence: 91%
“…Growing evidence shows that 4-hydroxyproline can scavenge oxidants (Phang et al 2010), suppress NF-kB activation (Ji et al 2018), regulate the intracellular redox state, and stimulate the expression of anti-oxidative enzymes in cells (Wu et al 2019). Furthermore, 4-hydroxyproline inhibits the production of hydroxyl radical via the Fenton reaction possibly through: (a) formation of coordinate bonds with iron, (b) sequestration of Fe 2+ , and (c) interactions with intermediates of the reaction via hydrophobic hydration (Milić et al 2015). In vitro anti-oxidative effects (e.g., scavenging of radicals and inhibition of lipid peroxidation) have also been demonstrated for the enzymatic hydrolysates of porcine collagen (Ao and Li 2012).…”
Section: Physiological Functions Of 4-hydroxyprolinementioning
confidence: 95%